(untitled) (Docentes 2.0 Journal, 2024)
A global priority in the educational context is the application of Information and Communication Technologies in teaching and learning. Therefore, it is a priority for educators to strengthen their digital skills and empower themselves using a set of digital resources. The study aimed to analyze digital competencies and the integration of ICT in the teaching-learning process in higher education. It was based on a systematic literature review following the PRISMA protocol. A descriptive, documentary and exploratory approach was chosen. The Scopus, Eric, and SciELO databases were used, and inclusion and exclusion criteria were applied, which allowed the selection of 10 scientific resources for the study. The analysis of the results reveals that digital teaching competencies and the incorporation of ICT at the higher level have undergone a significant adoption process. In conclusion, in an increasingly digitized world, teachers must be prepared to face the challenges of the digital age and take advantage of the opportunities provided by ICTs to improve the quality of teaching and learning.